Parents' Knowledge Level About First Aid For Children Experiencing Fever Seizures In Sei Mencirim Village, Sei Mencirim Public Health Center, Sunggal District, Deli Serdang Regency In 2025 - Nove Kasman Sarful Zendrato; Indra H. Perangin-angin; Ance M. Siallagan (PT. Padang Tekno Corp, 2026)
Febrile seizures are a common emergency in children aged 6 months to 5 years and can cause significant anxiety in parents. Proper early management of febrile seizures largely depends on parent's knowledge as the primary caregivers. Inadequate knowledge may lead to inappropriate first aid measures that can worsen the child's condition. This research aims to identify the level of parent's knowledge regarding first aid management for children experiencing febrile seizures in Sei Mencirim. This study uses a descriptive design method with a cross-sectional approach. The population in this study are all parents who brought their children for treatment to the Sei Mencirim Community Health Center in the last three months, wiht a sample of 36 respondents taken using an accidental sampling technique. The research instrument is a questionnaire consisting of 25 questions. Data analysis was carried out univariately to describe the level of respondents' knowledge. The results of the study show that parental knowledge based on the management of febrile seizures, parents have a good level of knowledge of 55.6%. Based on the administration during seizures, parental knowledge is in the sufficient category of 38.9%. Based on the administration of medication from the hospital after the child is treated, parental knowledge is in the good category off 66.7%. Based on information about seizures, parental knowledge is in the good category of 75.0%. concluded that the level of parental knowledge about first aid for children experiencing febrile is in the good category of 80.5%.